Hubungan Aktivitas Menonton Pornografi dengan Perilaku Pelecehan Seksual pada Siswa - Hardian, Ruzi; Karneli, Yeni (Lembaga Yasin AlSys, 2025)
The increasing prevalence of sexual harassment among students has become a serious concern in the field of education, particularly in relation to the growing accessibility of pornographic content through digital devices. This article aims to: (1) describe the students’ pornography viewing activities, (2) describe the sexual harassment behaviors among students, and (3) examine the relationship between pornography viewing and sexual harassment behavior among students. The study employed a quantitative approach with a descriptive-correlational design. The population consisted of 235 male students in grades X, XI, and XII at SMAN 5 Pariaman during the 2024/2025 academic year, with a sample of 148 students selected using Proportional Stratified Random Sampling. Data were collected through questionnaires on pornography viewing activities and sexual harassment behavior. The results indicate that both pornography viewing and sexual harassment behaviors are at a moderate level, suggesting that these behaviors occur with sufficient frequency to potentially disrupt the school environment. Correlational analysis revealed a strong positive relationship between the intensity of pornography viewing and the tendency to engage in sexual harassment. Contributing factors include the ease of access to pornography, lack of parental and teacher supervision, and limited sexual education in schools. These findings offer practical implications for parents, teachers, and educational policymakers to strengthen monitoring systems, provide comprehensive sexual education, and create a safe and supportive school environment.